Answer:
49
Step-by-step explanation:
Positive 49 not -49
Answer:
For k = 6 or k = -6, the equation will have exactly one solution.
Step-by-step explanation:
Given a second order polynomial expressed by the following equation:
.
This polynomial has roots
such that
, given by the following formulas:
![x_{1} = \frac{-b + \sqrt{\bigtriangleup}}{2*a}](https://tex.z-dn.net/?f=x_%7B1%7D%20%3D%20%5Cfrac%7B-b%20%2B%20%5Csqrt%7B%5Cbigtriangleup%7D%7D%7B2%2Aa%7D)
![x_{2} = \frac{-b - \sqrt{\bigtriangleup}}{2*a}](https://tex.z-dn.net/?f=x_%7B2%7D%20%3D%20%5Cfrac%7B-b%20-%20%5Csqrt%7B%5Cbigtriangleup%7D%7D%7B2%2Aa%7D)
![\bigtriangleup = b^{2} - 4ac](https://tex.z-dn.net/?f=%5Cbigtriangleup%20%3D%20b%5E%7B2%7D%20-%204ac)
If
, the equation has only one solution.
In this problem, we have that:
![3x^{2} + kx + 3 = 0](https://tex.z-dn.net/?f=3x%5E%7B2%7D%20%2B%20kx%20%2B%203%20%3D%200)
So
![a = 3, b = k, c = 3](https://tex.z-dn.net/?f=a%20%3D%203%2C%20b%20%3D%20k%2C%20c%20%3D%203)
![\bigtriangleup = b^{2} - 4ac](https://tex.z-dn.net/?f=%5Cbigtriangleup%20%3D%20b%5E%7B2%7D%20-%204ac)
![\bigtriangleup = k^{2} - 4*3*3](https://tex.z-dn.net/?f=%5Cbigtriangleup%20%3D%20k%5E%7B2%7D%20-%204%2A3%2A3)
![\bigtriangleup = k^{2} - 36](https://tex.z-dn.net/?f=%5Cbigtriangleup%20%3D%20k%5E%7B2%7D%20-%2036)
We will only have one solution if
. So
![\bigtriangleup = 0](https://tex.z-dn.net/?f=%5Cbigtriangleup%20%3D%200)
![k^{2} - 36 = 0](https://tex.z-dn.net/?f=k%5E%7B2%7D%20-%2036%20%3D%200)
![k^{2} = 36](https://tex.z-dn.net/?f=k%5E%7B2%7D%20%3D%2036)
![k = \pm \sqrt{36}](https://tex.z-dn.net/?f=k%20%3D%20%5Cpm%20%5Csqrt%7B36%7D)
![k = \pm 6](https://tex.z-dn.net/?f=k%20%3D%20%5Cpm%206)
For k = 6 or k = -6, the equation will have exactly one solution.
Answer:
look it up
Step-by-step explanation:
Try and find a way to look it up.
Answer:
80
Step-by-step explanation:
add
Answer:
1.0080 x 10^4
Step-by-step explanation:
in scientific notation the number has to be less then 10
10080 / 10000 = 1.0080
1.0080 x 10^4